Occurrence of Tomato yellow leaf curl virus and Tomato chlorosis virus mixed infections in protected tomato plants, Antalya, Turkey - Gul-Seker, Mine; Elibuyuk, I. Ozer (Springer, 2019)
During the autumn of 2011, upward leaf cupping, curling, chlorosis on the upper leaves, and interveinal chlorosis on the lower leaves of some protected tomato plants was observed in Antalya, Turkey. These symptoms indicated possible virus infection in tomato plants. Due to the symptoms, these plants could possibly have Tomato yellow leaf curl virus (TYLCV), Tomato infectious chlorosis virus (TICV), and/or Tomato chlorosis virus (ToCV) infections. Consequently, 300 greenhouses were surveyed. Because there are two cultivation periods, spring and autumn, in Antalya, the study was conducted over two periods. No mixed infections were detected during the spring season, however in autumn cultivation symptomatic tomato leaf samples from 17 greenhouses, tested with enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR), were found to have mixed infections of TYLCV and ToCV. This indicated that TYLCV/ToCV mixed infection was present in about 9.3% of the greenhouses. The symptoms ranged from moderate (slight curling in upper leaves and slight leaf chlorosis in lower leaves) to severe (severe curling and extensive chlorosis in upper leaves, stunting, greatly reduced fruit set, and conspicuous chlorosis in lower leaves). This is the first report of TYLCV/ToCV mixed infections in Turkey.
Keywords: Tomato; Begomovirus; Crinivirus; PCR; ELISA